Peran moderasi manajemen laba dalam hubungan ESG disclosure, working capital turnover, dan konservatisme terhadap kinerja keuangan - Azlya, Chalida Nashwa; Arismaya, Anisa Dewi (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2025)
This study examines the relationship between Environmental, Social, and Governance (ESG) disclosure, working capital turnover, and accounting conservatism on financial performance, with earnings management as a moderating variable, in companies listed on the Jakarta Islamic Index 30 (JII 30) from 2019 to 2023. This study employs a quantitative approach with purposive sampling, yielding a research sample of 65 observations. Panel data were analysed using Moderated Regression Analysis (MRA). The results indicate that environmental disclosure has no significant impact on financial performance. In contrast, social disclosure has a negative and significant effect, and governance disclosure has a positive but insignificant effect. Furthermore, working capital turnover and accounting conservatism both exhibit adverse and significant effects on financial performance. The MRA results indicate that earnings management does not moderate the effects of ESG disclosure, working capital turnover, and accounting conservatism on financial performance.